The Practice of Non-Litigation Mediation in Resolving Family Conflicts from the Perspective of Supreme Court Regulation Number 1 of 2016 - Abdullah Deri Humaidi; Jamiliya Susantin; Muhammad Habiburrahman (At-Tafkir, 2026)
This study examines the practice of non-litigation mediation in resolving family conflicts from the perspective of Supreme Court Regulation Number 1 of 2016, with a case study conducted in Tlanakan Village, Pamekasan Regency. The study addresses the gap between formal mediation regulations and the persistence of informal mediation practices within society. This research employs an empirical legal approach using qualitative methods through observation, in-depth interviews, and documentation. The findings reveal that non-litigation mediation is primarily conducted by religious leaders, community figures, and family elders through informal and flexible processes grounded in local wisdom. Substantively, these practices reflect the principles of good faith, deliberation, and peaceful settlement in accordance with the values embodied in Supreme Court Regulation Number 1 of 2016. However, procedurally, the mediation practices have not fully met formal legal standards due to the absence of certified mediators, guarantees of neutrality, and legally binding agreements. The study concludes that non-litigation mediation is socially effective in preserving family harmony and preventing conflict escalation, yet remains juridically weak in ensuring legal certainty and protection for vulnerable parties. The implications of this research indicate the need for an integrative mediation model that combines local wisdom-based practices with formal legal standards through mediator training, procedural strengthening, and legal recognition of mediation outcomes. This study contributes theoretically to the discourse on legal pluralism and practically to the development of more adaptive and community-oriented family dispute resolution mechanisms in Indonesia.